PRELIMINARY OBSERVATIONS ON MICROBIAL DIVERSITY FROM KRISHNA MANGROVES AT PALAKAYATIPPA, HAMSALADEVI IN ANDHRA PRADESH ON THE EAST COAST OF INDIA - K.HARI BABU; D.RAVI TEJA; K.RAMANESWARI (International Journal of Pharma and Bio Sciences, 2012)
The present study reports the occurrence of different microbial population at Palakayatippa, Hamsaladevi of Krishna mangrove area which is the first of its kind. Rhizosphere soil and sediment samples were collected and used for microbial isolation through pour plate method. The different groups were observed bacteria, fungi and actinomycetes. The study reveals that different types of pigment producing fungi and actinomycetes were predominant.